Effectiveness of Digital Forensic Evidence Examination Through the Scientific Crime Investigation Method in Proving Narcotics Crimes at the Forensic Laboratory Division of Riau Regional Police - Ungkap Siahaan; Donny Setha; D. K. Dewi (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This study aims to analyze the effectiveness of digital forensic evidence examination through the Scientific Crime Investigation (SCI) method in proving narcotics-related criminal offenses at the Forensic Laboratory Division (Bidlabfor) of the Riau Regional Police. This research employs an empirical legal approach with a qualitative method using a multi-case study design. Data were collected through semi-structured interviews, direct observation, and document analysis, and analyzed using the interactive model of Miles and Huberman, guided by the principles of due process of law and chain of custody, as well as Friedman’s legal system theory. The findings indicate that, normatively, the implementation of legal principles and examination procedures is adequate; however, empirically, it remains suboptimal due to limitations in human resources, technological facilities, and the lack of up-to-date digital forensic software. The effectiveness of the SCI method in legal proof is also not fully convincing, as forensic examination results still require reinforcement through expert testimony in court. Furthermore, the effectiveness constraints are influenced by structural, substantive, and legal cultural factors that have not fully supported the optimization of digital-based evidence. Therefore, strengthening institutional capacity, updating regulatory frameworks, and enhancing the competence of law enforcement officers are necessary to improve the quality and evidentiary value of digital forensic analysis in narcotics crime cases.